Narrative structure of literary text: Free indirect discourse as a linguistic and narratological category - Jourdy, Natascha (Glottodidactica, 2009)
The paper focuses on the analysis of free indirect discourse as a modernist narrative form. We outline the basic narrative and linguistic characteristics of free indirect discourse and examine its main functions in the literary texts. We undertake a comparative analysis of three examples of free indirect discourse (drawn from the texts of G. Flaubert, F. Kafka and V. Nabokov) and display their common and distinctive features.